Association between adrenergic receptor genotypes and beta‐blocker dose in heart failure patients: analysis from the HF‐ACTION DNA substudy. (March 2013) - Fiuzat, Mona; Neely, Megan L.; Starr, Aijing Z.; Kraus, William E.; Felker, G. Michael; Donahue, Mark; Adams, Kirkwood; Piña, Ileana L.; Whellan, David; O'Connor, Christopher M.
<x xml:space="preserve">Abstract</x> Aims Beta‐blockers reduce morbidity and mortality in chronic heart failure (HF) patients with reduced ejection fraction. However, there is heterogeneity in the response to these drugs, perhaps due to genetic variations in the β1‐adrenergic receptor (ADRβ1). We examined whether the Arg389Gly polymorphism in ADRβ1 interacts with the dose requirements of beta‐blockers in patients with systolic HF. Methods and results HF‐ACTION was a randomized, multicentre trial of ambulatory HF patients with systolic dysfunction who were randomized to exercise training or usual care. A subset of patients provided DNA. The relationships among beta‐blocker dose, ADRβ1–389 genotype, and outcomes were assessed using the Cox proportional hazards regression model. The interaction between beta‐blocker dose and the ADRβ1–389 genotype was tested. DNA information was available for 957 patients. The alleles did not deviate from Hardy–Weinberg equilibrium. Patients with the ADRβ1–389 Arg/Arg genotype receiving low‐dose beta‐blockers had a two‐fold increase in the risk of death compared with those receiving a high dose (hazard ratio 2.09; P = 0.015); this was not conferred in Gly carriers. There was also an interaction between improvements in Kansas City Cardiomyopathy Questionnaire score and beta‐blocker dose by genotype, suggesting that higher doses of beta‐blockade might be needed to achieve benefit in Arg/Arg genotype patients. Conclusion There was a gene–dose interaction with the ADRβ1–389 Arg/Arg vs. Gly carrier genotype and beta‐blocker dose, suggesting that patients with the Arg/Arg genotype might require a higher dose of beta‐blockade to achieve a treatment response similar to that of Gly carriers.